Project management metrics, KPIs, and dashboards : a guide to measuring and monitoring project performance - Kerzner, Harold (New Jersey John Wiley & Sons. Inc., 2013)
This book helps functional managers gain a thorough grasp of what metrics and KPIs are and how to use them, as well as an understanding of different dashboard types, design issues, and applications.
Includes index.
osa 24/10/17
Loans
Keywords: Project management; Project management---Quality control; Performance standards; Work measurement